Enhanced Fc receptor expression by a sub-population of murine intra-tumour macrophages following intravenous Corynebacterium parvum therapy. - Moore, K. (Nature Publishing Group, 1983)
Intravenous injection of Corynebacterium parvum (C. parvum) 4 days after s.c. inoculation of 5 X 10(5) cells derived from the immunogenic fibrosarcoma FSA/R induced tumour growth inhibition over a period of 21 days in syngeneic C3H/Buf mice. This was not accompanied by a change in the proportions of host cells within the tumour, but the activation state of tumour-infiltrating macrophages was increased following C. parvum therapy. Two macrophage subpopulations were identified in FSA/R tumours after fractionation by unit gravity velocity sedimentation. After i.v. C. parvum therapy the tumour-infiltrating macrophage subpopulation which sedimented between 1 and 6 mm h-1 was consistently activated as determined by measurement of Fc receptor avidity. Other intra-tumour macrophages were generally unaffected by C. parvum treatment. We have previously shown that the host cell fraction sedimenting between 1 and 6 mm h-1 is enriched with monocytes and the data presented in this paper suggest that these cells may enter the tumour in a pre-activated state following intravenous C. parvum therapy.